KONSTRUKSI SOSIAL MASYARAKAT MELALUI KONTEN EDUKATIF MENGENAI KETAHANAN AIR - Desi Yunita; Bintarsih Sekarningrum (Universitas Padjadjaran, 2021)
This activity is intended to increase public awareness about why water resilience is important. Efforts to improve community water resilience done by providing educational content containing messages on water resilience through booklets, posters, animations, or short videos about how to increase water resilience practically by the community. So that the message of this water resilience campaign is spread to the wider community, these educational media are disseminated online via social media or shared directly when done face-to-face virtually. The method of dissemination through dissemination through social media or virtual presentations is chosen so that the message can be received appropriately while maintaining health protocols. So, even though it is still hit by a pandemic, the public can still be invited to participate in this activity.